E.FFECT OF HARVESTING TECHNIQUE AND OTHER FACTORS ON · OOCYTE RETRIEVAL IN BUFFALO (BUBALUS BUBALIS) - RAO, M MUTHA; MAHESH, Y UMA (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken to assess the ovarian biometry, follicular population and oocyte rec9very in buffalo ovaries obtained from a local abattoir. Three harvesting techniques viz., aspiration, puncture and slicing methods were employed to recover oocytes. Effect of ovarian status (luteal phase vs. non-luteal phase), ovarian volume (<1.5 cm3 vs. >1.5 cm 3 ), side of ovary Right vs. left) and number of visible follicles (No follicles vs.1-5 follicles vs: 6-1 0 follicles) on oocyte yield and quality were analyzed. The ovarian biometry (length, width, thickness, volume and weight) and the number of visible follicles did not differ significantly between left and right ovaries. The number of visible follicles were significantly higher (P<0.01) in non-luteal phase ovaries (2. 78 ±0.16) compared to luteal phase ovaries (1.97 ±0.19). Among the three collection methods, slicing technique yielded highest no. of total and good quality oocytes respectively (7.98 ± 0.70 and 3.23 ± 0.30) followed by puncture (3.46 ± 0.31 and 1.25 ± 0.17) and aspiration methods (2.38±0.19 and 0.84 ± 0.10). Irrespective of the method employed, a little over 1/3 o·f __ recovered oocytes were of poor quality (32.46- 34.34%). Luteal phase ovaries (having CL) yielded lower no. of oocytes compared to non-luteal phase (no CL) ovaries. Both left and right ovaries contributed equally to total as well as different quality grades of oocytes in all the methods. Ovarian velum non-significantly affected the oocyte yield which was slightly higher in ovaries with a mean volume >1.5 cm3 • The results indicate that slicing method is superior to the other two methods employed in this study to harvest more number of good quality as well as culture grade oocytes from buffalo ovaries.